Pengembangan Produk Mie dengan Substitusi Tepung Cangkang Rajungan (Portunus Pelagicus) Berbasis Laut Sebagai Produk Alternatif Yang Tinggi Fosfor - Sintha Fransiske Simanungkalit; Hilmy Mumtaz; Nadia Fahira Dewi; Puspaningrum Dwi Hartanti; Hendry Roris P Sianturi (Universitas Airlangga, 2026)
Background: Noodles represent a widely consumed source of carbohydrates in Indonesia; however, they have limited nutritional value. Objectives: To evaluate the effect of substituting crab shell flour as an alternative ingredient in noodle formulations to increase protein, calcium, and phosphorus content. Methods: This study used a completely randomized design (CRD) with one factor and five treatments. Each formulation contained 100 g of crab-shell or wheat flour. Protein was analyzed by the Kjeldahl method, and calcium and phosphorus by spectrophotometry. Organoleptic testing involved 40 panelists. Data were analyzed using one-way ANOVA with Duncan’s post hoc test and Kruskal–Wallis with Mann–Whitney tests. Results: The results demonstrated that treatment F5 had the highest calcium and phosphorus levels. However, the protein content showed variability. This variability may have resulted from the processing method used and the storage conditions of the product, which may affect protein stability. The results of the organoleptic test indicated that the F0 treatment noodles made entirely of wheat flour were the most preferred in terms of color and taste. Conclusions: The treatment F5 yielded the highest calcium and phosphorus levels, while treatment F0 had the highest protein content. Fluctuations in protein content may be attributed to the processing methods and storage conditions employed. The results of the organoleptic tests Indicated that F0 treatment noodles were the most preferred in terms of color and taste, while F1 treatment was still acceptable but with lower preference scores.